Motion Control of Under-actuated Aerial Robotic Manipulators - Jafarinasab, Mohammad (My University, 2018)
This thesis presents model-based adaptive motion control algorithms for under-actuated aerial robotic manipulators combining a conventional multi-rotor Unmanned Aerial Vehicle (UAV) and a multi-link serial robotic arm. The resulting control problem is quite challenging due to the complexity of the combined system dynamics, under-actuation, and possible kinematic redundancy. The under-actuation imposes second-order nonholonomic constraints on the system motion and prevents independent control of all system degrees of freedom (DOFs). Desired reference trajectories can only be provided for a selected group of independent DOFs, whereas the references for the remaining DOFs must be determined such that they are consistent with the motion constraints. This restriction prevents the application of common model-based control methods to the problem of this thesis. Using insights from the system under-actuated dynamics, four motion control strategies are proposed which allow for semi-autonomous and fully-autonomous operation. The control algorithm is fully developed and presented for two of these strategies; its development for the other two configurations follows similar steps and hence is omitted from the thesis. The proposed controllers incorporate the combined dynamics of the UAV base and the serial arm, and properly account for the two degrees of under-actuation in the plane of the propellers. The algorithms develop and employ the second-order nonholonomic constraints to numerically determine motion references for the dependent DOFs which are consistent with the motion constraints. This is a unique feature of the motion control algorithms in this thesis which sets them apart from all other prior work in the literature of UAVmanipulators. The control developments follow the so-called method of virtual decomposition, which by employing a Newtonian formulation of the UAV-Manipulator dynamics, sidesteps the complexities associated with the derivation and parametrization of a lumped Lagrangian dynamics model. The algorithms are guaranteed to produce feasible control commands as the constraints associated with the under-actuation are explicitly considered in the control calculations. A method is proposed to handle possible kinematic redundancy in the presence of second-order motion constraints. The control design is also extended to include the propeller dynamics, for cases that such dynamics may significantly impact the system response. A Lyapunov analysis demonstrates the stability of the overall system and the convergence of the motion tracking errors. Experimental results with an octo-copter integrated with a 3 DOF robotic manipulator show the effectiveness of the proposed control strategies.
Keywords: Motion control, under-actuation, nonholonomic, virtual decomposition, model-based, adaptive control, kinematic redundancy, multi-body system, aerial robotic, UAV, manipulator